Clinical Values of serum carcinoembryonic antigen (CEA), glycoprotein antigen (CA) 50, CA19-9, and CA72-4, and the soluble fragment of cytokeratin 19 (CYFRA21-1) in early screening and prognosis prediction of colon cancer: Clinical values of serum tumor markers - Zhang, Yingqiang; Song, Ze; Tang, Jun; Wu, Min; Li, Zhi (Journal of Medical Biochemistry, 2025)
aim: To investigate the clinical values of serum tumor markers carcinoembryonic antigen (CEA), glycoprotein antigen (CA) 50, CA19-9, and CA72-4, and the soluble fragment of cytokeratin 19 (CYFRA21-1) in early screening and prognosis prediction of colon cancer. Methods: 50 patients with colon cancer were enrolled into case group and 50 healthy people undergoing physical examination were enrolled into control group. The expressions of CEA, CA50, CA19-9, CA72-4, and CYFRA21-1 in two groups were compared. Results: It was demonstrated that the expressions of CEA, CA50, CA19-9, CA72-4, and CYFRA21-1 among patients in case group were all superior to those among patients in control group (P<0.05), and the expressions of four tumor markers among patients in late group were remarkably superior to those among patients in early group (P<0.05). Postoperative expressions of CEA, CA50, CA19-9, CA72-4, and CYFRA21-1 were notably inferior to preoperative expressions (P<0.05). However, the expressions were apparently higher before treatment when postoperative recurrence and metastasis occurred (P<0.05). The positive detection rates of the combined detection of CA50, CA19-9, CA72-4, and CYFRA21-1 for recurrence and metastasis were all markedly superior to those of single indicator detection (P<0.05). Conclusion: Tumor markers CEA, CA50, CA19-9, CA72-4, and CYFRA21-1 showed indication significance for detecting positive detection rate, tumor staging, and recurrence and metastasis of colon cancer. The combined detection could improve the detection rate of colon cancer and was conducive to early screening of colon cancer and the determination of prognosis of colon cancer.